KORELASI ANTARA DEHIDRASI DENGAN FAKTOR-FAKTOR KLINIS PADA ANAK KAMBING KACANG LOKAL (Capra aegagrus hircus)(Correlation between Dehydration and Assessment Clinical Factors in Kacang Goatlings (Capra aegagrus hircus)) - Roslizawaty Roslizawaty; Rusli Rusli; Isra Hadi; T. Fadrial Karmil; Amiruddin Amiruddin; Syafruddin Syafruddin (Jurnal Medika Veterinaria, 2016)
The purpose of this study was to determine the dominant factor that clinically influent the occurrence of dehydration in goats aged 10-14 days old, in order to enhance the accuracy in diagnoinge the state of hydration. Ten native kacang goatlings were used as research objects. Kacang goatlings were dehydrated until loss 10% of their bodyweight by inducing diuretics furosemide (2mg/kg body weight every 4 hours) using intramuscularly, orally administration of spironolactone (50 mg every 8 hours) and hydrochlorothiazide (50 mg every 8 hours). Regression analysis was used to verify the correlation between clinical factors that considered potential, which are enopthalmus, skin turgor (back, neck and upper eyelid), capillary refill time, pulsus, breath, and body temperature. The results showed that enopthalmus, skin turgor on back and eye region has close correlation with dehydration occurrence with coefficient determinant R2 are 0.92; 0.90 and 0.81 respectively. It can be concluded that these three parameters can be used as predictor towards dehydration occurrence.